Economic harmony: An epistemic theory of economic interactions - Ramzi Suleiman (Games, 2017)
We propose an epistemic theory of micro-economic interactions, termed Economic Harmony. In the theory, we modify the standard utility, by changing its argument from the player's actual payoff, to the ratio between the player's actual payoff and his or her aspired payoff. We show that the aforementioned minor epistemic modification of the concept of utility is quite powerful in generating plausible and successful predictions of experimental results, obtained in the standard ultimatum game, and the sequential common pool resource dilemma (CPR) game. Notably, the cooperation and fairness observed in the studied games are accounted for without adding an other-regarding component in the players' utility functions. For the standard ultimatum game, the theory predicts a division of φ and 1 - φ, for the proposer and responder, respectively, where φ is the famous Golden Ratio (≈0.618), most known for its aesthetically pleasing properties. We discuss possible extensions of the proposed theory to repeated and evolutionary ultimatum games.
Keywords: 330; epistemic; aspiration level; fairness; ultimatum game; common pool resource dilemma; golden ratio; Fibonacci numbers